Integrating Prevention of Mother-to-Child Transmission of HIV Care into General Maternal Child Health Care in Western Kenya - Michelle Berlacher; Timothy Mercer; Edith O. Apondi; Winfred Mwangi; Edwin Were; Megan S. McHenry (Global Health and Education Projects, Inc., 2020)
Background: Health systems integration is becoming increasingly important as the global health community transitions from acute, disease-specific health programming to models of care built for chronic diseases, primarily designed to strengthen public-sector health systems. In many countries across sub-Saharan Africa, including Kenya, prevention of mother-to-child transmission of HIV (pMTCT) services are being integrated into the general maternal child health (MCH) clinics. The objective of this study was to evaluate the benefits and challenges for integration of care within a developing health system, through the lens of an evaluative framework. Methods: A framework adapted from the World Health Organization's six critical health systems functions was used to evaluate the integration of pMTCT services with general MCH clinics in western Kenya. Perspectives were collected from key stakeholders, including pMTCT and MCH program leadership and local health providers. The benefits and challenges of integration across each of the health system functions were evaluated to better understand this approach. Results: Key informants in leadership positions and MCH staff shared similar perspectives regarding benefits and challenges of integration. Benefits of integration included convenience for families through streamlining of services and reduced HIV stigma. Concerns and challenges included confidentiality issues related to HIV status, particularly in the context of high-volume, crowded clinical spaces. Conclusion and Global Health Implications: The results from this study highlight areas that need to be addressed to maximize the effectiveness and clinical flow of the pMTCT-MCH integration model. The lessons learned from this integration may be applied to other settings in sub-Saharan Africa attempting to integrate HIV care into the broader public-sector health system. Copyright © 2020 Berlacher et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.